Pengaruh Kompetensi Terhadap Kepuasan Kerja Pegawai Non Medis RSUD Banyuasin - Teuku Muhammad Haqiqi; Maisaro; Riri Hanifa (Journal of Management, Entrepreneur and Cooperative, 2022)
One of the key successes of the institutions to achieve their goal, is need professional and good quality human resources. The resourches should be innovative, having a commitment to support their functions and tasks the properly. This study aims to examine the influence of Competence on Job Satisfaction Non-medical staff in RSUD Banyuasin with Simple linear Regression. This study uses Competency as independent variable, Job Satisfaction as dependent variable. Methods of data analysis of this study using quantitative data analysis, and using descriptive research. The primary data are collected by using the questionnaire distributed to respondents. The test results show that the competence of positive and significant impact on the job satisfaction.